What to Reveal, What to Conceal. The Theatre of the Real and the Confession Under Control - Iulia Popovici (Symbolon, 2020)
In the following paper, I will try to analyze the specific strategies used in the case of Romanian socially engaged fact-based productions in order to install the convention of reality on which the spectatorial response is based in the case of such performances, how these strategies and the convention itself can be manipulated and what kind of consequences this manipulation entails, using the example of a theatre piece which aims at questioning the fetishization of truthfulness.